2008
DOI: 10.1016/j.heares.2007.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing cochlear implant patients’ performance with advanced speech training procedures

Abstract: Advances in implant technology and speech processing have provided great benefit to many cochlear implant patients. However, some patients receive little benefit from the latest technology, even after many years' experience with the device. Moreover, even the best cochlear implant performers have great difficulty understanding speech in background noise, and music perception and appreciation remain major challenges. Recent studies have shown that targeted auditory training can significantly improve cochlear im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
116
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(128 citation statements)
references
References 70 publications
(87 reference statements)
7
116
0
5
Order By: Relevance
“…One of the common findings from the studies of CI users is individual variability in their speech recognition scores regardless of speech materials or noise conditions (e.g., Fu & Galvin, 2008;Gifford, Shallop, & Peterson, 2008;Kwon et al, 2012), which was also found in the current study. Table 6 shows the performance of individual CI listeners in several conditions: quiet with full-spectrum speech and low-pass filtered speech, remote noise for the three AM conditions, and embedded noise for the same AM conditions.…”
Section: Clinical Implications For CI Listenerssupporting
confidence: 83%
See 2 more Smart Citations
“…One of the common findings from the studies of CI users is individual variability in their speech recognition scores regardless of speech materials or noise conditions (e.g., Fu & Galvin, 2008;Gifford, Shallop, & Peterson, 2008;Kwon et al, 2012), which was also found in the current study. Table 6 shows the performance of individual CI listeners in several conditions: quiet with full-spectrum speech and low-pass filtered speech, remote noise for the three AM conditions, and embedded noise for the same AM conditions.…”
Section: Clinical Implications For CI Listenerssupporting
confidence: 83%
“…If this is true, then peripheral manipulations on the current commercial CI devices such as developments in signal processing algorithms or mapping strategies might not be enough to reduce the negative effect of background noise on speech perception of CI listeners. Perhaps, specific auditory training such as speech-in-noise training or targeted speech training in modulated maskers could be recommended based on listeners' individual needs (Fu & Galvin, 2008).…”
Section: Clinical Implications For CI Listenersmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors emphasize that speech perception of implant users can be improved by more formalized auditory training consisting of repetitive exercises focused on the speech perception skill to be learned, such as hearing through the telephone. Positive results have been found with only a small amount of training and transfer of learning to untrained speech tests (Fu & Galvin, 2008;Moore, Ferguson, Halliday, & Riley, 2008). These studies suggest that, despite the fact that the implant signal may limit the speech perception performance level, most individuals can benefit from training, indicating that they have not extracted all the information available from the signal before the training.…”
Section: Limitations Of Cochlear Implants For Speech Perceptionmentioning
confidence: 98%
“…Por esse motivo, é ressaltada a importância da atenção do fonoaudiólogo durante as situações terapêuticas, para que aproveite os indícios da criança de que está apta a ser desafiada com tarefas de maior complexidade; ou de que necessita de retomada de habilidades mais iniciais -como a discriminação auditiva, que em quase todos os casos precisa ser trabalhada durante todo o processo de terapia fonoaudiológica aurioral, mesmo quando a criança já está no nível da compreensão auditiva. Isso porque, apesar de ela ser capaz de reconhecer ou compreender conteúdos no contexto, informações específicas podem ser perdidas, como os traços distintivos dos fonemas e os traços supra-segmentais (FU; GALVIN, 2008).…”
Section: Planos Diáriosunclassified